2015
DOI: 10.1007/s00384-015-2164-3
|View full text |Cite
|
Sign up to set email alerts
|

A clinical model for predicting lymph node metastasis in submucosal invasive (T1) colorectal cancer

Abstract: Combined evaluation of infiltrative growth pattern, lymphoid infiltration, poorly differentiated carcinoma, and sessile appearance showed good performance for discriminating T1-CRC patients with LNM. The benefit-risk balance was in favor of surgery when at least two of these criteria were present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…The literature search revealed 2728 publications ( Figure 2 ). Of the 143 included for full text review, 34 were ultimately included in the meta-analysis ( Hase et al , 1993 ; Ueno et al , 2002a ; Okuyama et al , 2003a , 2003b ; Ueno et al , 2004 ; Prall et al , 2005 ; Wang et al , 2005 ; Yasuda et al , 2007 ; Kanazawa et al , 2008 ; Nakamura et al , 2008 ; Yamauchi et al , 2008 ; Lugli et al , 2009 ; Ogawa et al , 2009 ; Wang et al , 2009 ; Homma et al , 2010 ; Kajiwara et al , 2010 ; Komori et al , 2010 ; Tateishi et al , 2010 ; Akishima-Fukasawa et al , 2011 ; Reggiani Bonetti et al , 2011 ; Betge et al , 2012 ; Nakadoi et al , 2012 ; Sert Bektas et al , 2012 ; Zlobec et al , 2012 ; Wada et al , 2013 ; Huh et al , 2014 ; Lai et al , 2014 ; Nishida et al , 2014 ; Ryu et al , 2014 ; Gilardoni et al , 2015 ; Macias-Garcia et al , 2015 ; Miyachi et al , 2015 ; Tristante et al , 2015 ; Barresi et al , 2016 ). There were a total of 7821 patients included for analysis, with study groups ranging from 58 to 1114 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search revealed 2728 publications ( Figure 2 ). Of the 143 included for full text review, 34 were ultimately included in the meta-analysis ( Hase et al , 1993 ; Ueno et al , 2002a ; Okuyama et al , 2003a , 2003b ; Ueno et al , 2004 ; Prall et al , 2005 ; Wang et al , 2005 ; Yasuda et al , 2007 ; Kanazawa et al , 2008 ; Nakamura et al , 2008 ; Yamauchi et al , 2008 ; Lugli et al , 2009 ; Ogawa et al , 2009 ; Wang et al , 2009 ; Homma et al , 2010 ; Kajiwara et al , 2010 ; Komori et al , 2010 ; Tateishi et al , 2010 ; Akishima-Fukasawa et al , 2011 ; Reggiani Bonetti et al , 2011 ; Betge et al , 2012 ; Nakadoi et al , 2012 ; Sert Bektas et al , 2012 ; Zlobec et al , 2012 ; Wada et al , 2013 ; Huh et al , 2014 ; Lai et al , 2014 ; Nishida et al , 2014 ; Ryu et al , 2014 ; Gilardoni et al , 2015 ; Macias-Garcia et al , 2015 ; Miyachi et al , 2015 ; Tristante et al , 2015 ; Barresi et al , 2016 ). There were a total of 7821 patients included for analysis, with study groups ranging from 58 to 1114 patients.…”
Section: Resultsmentioning
confidence: 99%
“…There were considerable differences and an overt lack of standardisation of tumour budding between studies ( Table 2 ). Twenty-eight studies used standard haematoxylin and eosin (H&E) staining, four studies used immunohistochemistry (IHC) and cytokeratin staining ( Prall et al , 2005 ; Lugli et al , 2009 ; Ogawa et al , 2009 ; Zlobec et al , 2012 ), and two did not specify the technique ( Gilardoni et al , 2015 ; Macias-Garcia et al , 2015 ), although one could assume standard H&E was used. A ‘budding focus' or its equivalent was defined as an isolated cancer cell or cluster of less than five cells in 24 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Third, all the studies in this meta-analysis originated in Japan, which may have affected our results. Only 3 of the 36 studies were from western countries, none of which reported adjusted results, and were thus excluded from the current criteria (28,30,48). In fact, these 3 studies showed a tendency of higher LNM rate in female rather than in male patients, but the difference was not significant due to insufficient number (<100) of study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for regional lymph node metastasis is reported up to 14 percents of patients with T1 colorectal cancer 15, 16. Combing risk factors of lymph node metastasis, including large tumor size, old age, lymphatic invasion, submucosal invasion (≥1 mm), and poor differentiation, with high‐resonance magnetic imaging and computed tomography 12, 17, 18, 19, surgeons can identify patients with lower risk for lymph node metastasis, which are, by definition, clinic N0.…”
Section: Discussionmentioning
confidence: 99%